2015
DOI: 10.1142/s2010135x15500022
|View full text |Cite
|
Sign up to set email alerts
|

Studies of phase transition and impedance behavior of Ba(Zr, Ti)O3 ceramics

Abstract: Ceramic samples of Barium Zirconium Titanate (BaZr x Ti 1Àx O 3 (BZT)) were synthesized by conventional solid-state reaction method with different concentrations of x (¼ 0:05 (BZT1), 0.10 (BZT2), 0.15 (BZT3), 0.20 (BZT4), 0.25 (BZT5), 0.30 (BZT6)). Phase confirmation of the samples was done by X-ray diffraction (XRD) technique. All the compositions are in cubic structure. XRD pattern was recorded for samples sintered at different sintering temperatures. Lattice parameters increased with addition of Zr þ4 . Dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…More conveniently seen from the dielectric loss (tan δ), the dielectric anomaly was associated with a process of relaxation [17]: loss peaks shifted toward higher temperatures with an increase in the frequency (Figure 4c). The associated physical properties of BCTZ ceramics after T C are related to relaxation and conductivity processes [17][18][19][20][21]. For ferroelectric materials, it is important to perform a complete analysis of their electrical properties to separate different electroactive contributions (grain/bulk and grain boundary) and their frequency/temperature dependence.…”
Section: Dielectric Analysismentioning
confidence: 99%
“…More conveniently seen from the dielectric loss (tan δ), the dielectric anomaly was associated with a process of relaxation [17]: loss peaks shifted toward higher temperatures with an increase in the frequency (Figure 4c). The associated physical properties of BCTZ ceramics after T C are related to relaxation and conductivity processes [17][18][19][20][21]. For ferroelectric materials, it is important to perform a complete analysis of their electrical properties to separate different electroactive contributions (grain/bulk and grain boundary) and their frequency/temperature dependence.…”
Section: Dielectric Analysismentioning
confidence: 99%
“…Dielectric loss is higher at lower frequencies and decreases with an increase of frequency. It shows that at higher frequencies dipoles were unable to follow the applied AC field and hence, a decrease in dielectric loss at higher frequencies occurred [6][7][8]11]. Zhi et al [16] reported that dielectric constant value also depends on the density of the samples.…”
Section: Dielectric Studiesmentioning
confidence: 99%
“…This is due to the substitution of large size Zr 4+ cation (0.072 nm) in place of small size Ti 4+ cation (0.0605 nm) as this substitution depresses the oriented displacement of B-site ions in the oxygen octahedra. Therefore, the interaction between B-site ions and oxygen ions in the oxygen octahedra would become weaker, resulting in the decrease of phase transition temperature [1,2,8,9,11].…”
Section: Dielectric Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Barium zirconate titanate, Ba(Zr,Ti)O 3 (BZT) is a well-known stable lead-free ferroelectric material which finds many technological applications such as relaxor, [1][2][3][4][5] microwave, 6 high voltage, 7 high temperature, 8 actuator, 9 piezoelectric, [10][11][12] energy storage, 13 magnetoelectric. 14 Investigations have been taken up world-wide with different aims on the solid solutions of BZT with other materials like: (Ba,Ca)TiO 3 , [15][16][17][18][19] (Bi 1=2 Na 1=2 ÞTiO 3 , [20][21][22][23] 29 NiO, 30 Ni, 31 polyvinyl alcohol, 32 epoxy, 33 Portland cement, 34,35 etc.…”
Section: Introductionmentioning
confidence: 99%